Advanced Analysis and Design for Fire Safety of Steel Structures - Li, Guoqiang; Wang, Peijun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Advanced Analysis and Design for Fire Safety of Steel Structures systematically presents the latest findings on behaviours of steel structural components in a fire, such as the catenary actions of restrained steel beams, the design methods for restrained steel columns, and the membrane actions of concrete floor slabs with steel decks. Using a systematic description of structural fire safety engineering principles, the authors illustrate the important difference between behaviours of an isolated structural element and the restrained component in a complete structure under fire conditions. The book will be an essential resource for structural engineers who wish to improve their understanding of steel buildings exposed to fires. It is also an ideal textbook for introductory courses in fire safety for master$1 (Bs degree programs in structural engineering, and is excellent reading material for final-year undergraduate students in civil engineering and fire safety engineering. Furthermore, it successfully bridges the information gap between fire safety engineers, structural engineers and building inspectors, and will be of significant interest to architects, code officials, building designers and fire fighters. Dr. Guoqiang Li is a Professor at the College of Civil Engineering of Tongji University, China; Dr. Peijun Wang is an Associate Professor at the School of Civil Engineering of Shandong University, China.s
Fire in Building -- Properties of steel at elevated temperatures -- Fire-resistance of isolated steel components -- Fire-resistance of restrained flexural components -- Fire-resistance of restrained steel columns -- Fire-resistance of concrete slabs with steel deck -- Analysis of steel moment-resistant frames subjected to fire -- Analysis and design for large space steel structures subjected to fire.
Keywords: Engineering; Construction; Structural mechanics; Quality control; Reliability; Industrial safety; Buildings -- Design and construction; Building; Engineering, Architectural; Engineering; Structural Mechanics; Quality Control, Reliability, Safety and Risk; Basics of Construction; Building Construction; Electronic books